2001
DOI: 10.1002/1522-2683(200109)22:15<3178::aid-elps3178>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic study on the opposite migration order of clenbuterol enantiomers in capillary electrophoresis with β-cyclodextrin and single-isomer heptakis(2,3-diacetyl-6-sulfo)-β-cyclodextrin

Abstract: Opposite migration order was observed for the enantiomers of the chiral beta2-adrenergic drug clenbuterol (CL) in capillary electrophoresis (CE) when resolved with native beta-cyclodextrin (beta-CD) and heptakis (2,3-diacetyl-6-sulfo)-beta-CD (HDAS-beta-CD). The possible mechanisms of the affinity reversal of the CL enantiomers depending on the structure of the CD were studied using 1H-nuclear magnetic resonance (1H-NMR) spectrometry and one-dimensional rotating frame nuclear Overhauser and exchange spectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 47 publications
2
25
0
Order By: Relevance
“…There are different ways to change the enantiomeric migration order by CE when CDs are used as chiral selectors [4,[10][11][12][13]: (i) modifying the CD cavity size [14]; (ii) changing the nature of CD substituents [15,16]; (iii) varying the location of substituents on the CD rim [17]; (iv) employing charged CDs in the BGE and changing the polarity of the applied voltage [18,19]; (v) modifying the pH of the BGE [18,20]; (vi) changing the EOF, i.e., eliminating or reversing it [19,20]; (vii) using achiral additives (i.e., micelles or ligandexchange compounds as metals) in chiral systems [21,22], and finally, (viii) varying the concentration of the CD in the separation buffer. However, this last phenomenon has scarcely been observed.…”
Section: Introductionmentioning
confidence: 77%
“…There are different ways to change the enantiomeric migration order by CE when CDs are used as chiral selectors [4,[10][11][12][13]: (i) modifying the CD cavity size [14]; (ii) changing the nature of CD substituents [15,16]; (iii) varying the location of substituents on the CD rim [17]; (iv) employing charged CDs in the BGE and changing the polarity of the applied voltage [18,19]; (v) modifying the pH of the BGE [18,20]; (vi) changing the EOF, i.e., eliminating or reversing it [19,20]; (vii) using achiral additives (i.e., micelles or ligandexchange compounds as metals) in chiral systems [21,22], and finally, (viii) varying the concentration of the CD in the separation buffer. However, this last phenomenon has scarcely been observed.…”
Section: Introductionmentioning
confidence: 77%
“…A method development and validation with a well-characterized, singlecomponent chiral selector is much easier and reliable. Recent studies with single-isomer sulfates of b-CD revealed that they may offer alternative chiral recognition mechanisms compared to native b-CD [16][17][18]. Thus, the enantiomer affinity pattern of chiral drugs clenbuterol (CL) [16], warfarin [17] and promethazine (PMZ) [18] was opposite to native b-CD and heptakis-(2,3-diacetyl-6-sulfo)-b-CD (HDAS-b-CD).…”
Section: Introductionmentioning
confidence: 99%
“…Opposite migration order between b-CD and HS-b-CD on one hand and HDAS-b-CD on the other hand has also been observed for alanine b-naphthylamide [9] and a number on nonpeptide analytes [22][23][24].…”
Section: Ce Enantioseparationsmentioning
confidence: 75%